An Approach to the evaluation of blast loads on finite and semi-infinite structures - Rose, T. A. (Engineering Systems Department, 2010)
This thesis is concerned with the use of Computational Fluid Dynamics techniques coupled with experimental studies to establish useful relationships between explosively generated blast loads and the principal aspects of the geometry of both single buildings and many buildings, as might be found in any urban environment. A method for the treatment of blast loading problems is described which is based on a large number of numerical simulations validated by key physical experiments. The idea of using numerical simulation to investigate aspects of How problems which are too difficult, expensive or time-consuming to consider experimentally is not new. The emphasis of this thesis, however, is not the treatment of specific problems but whole classes of problems. Chapter l introduces the diiiiculties associated with the evaluation of blast loads on structures. It briefly describes several existing techniques and introduces the approach suggested by this study. It also contains a number of useful deinitions which assist ap- preciation of the difficulties of numerical simulation of blast loading. Chapter 2 is in the form of a narrative and describes the process by which the solu- tion algorithm of the program used for the blast simulations (Air3d) was selected. The final choice, AUSMDV (a variant of the Advection Upstream Splitting Method) with MUSCL-Hancock integration (MUSCL standing for “Monotone Upstream~centred Scheme for Conservation Laws”), is essentially the combination of two methods which are “cheap” in terms of computational resources to obtain one of only moderate “expense” but which has sufiicient accuracy and robustness for these demanding applications. Chapter 3 contains a description of the computational tool Air3d, and it acts as a user’s guide to the program. Chapter 3 also contains a discussion of the treatment by the program ,Air3d of the processes which govern the formation of spherical blast waves in air. The chapter concludes with a comparison between the results of Air3d and a commercially available program and demonstrates the eflicacy of the solution algorithm adopted. Chapter 4 demonstrates the potential of the approach to obtain useful information in the main areas of application (Chapters 5 to 7) in this thesis. This is achieved by comparison of Air3d simulations with established sets of experimentally determined scaled blast parameters. Chapter 5 describes the problem of blast wave clearing, or loads on single finite struc- tures, and uses the approach to produce a relationship which is applicable over almost the whole range of practical interest to engineers. Chapter 6 is concerned with the effect of street width and building height on the blast overpressure impulses which load the facades of a street when an explosive incident occurs in an urban setting. It considers semi-infinite straight streets and describes, in broad terms, the limits of width and height which determine the blast impulse loads. Chapter 7 contains a discussion of the blast environment behind a serni~infinite protec- tive barrier wall when an explosive device is detonated on the near side. This problem has particular diiiiculties, which are discussed, and has illustrated the limits of the suggested approach. Chapter 8 summarises the approach adopted by this study for blast load evaluation, and it describes the progress made, difficulties encountered and the limitations of the method. Recommendations are made which would improve the approach for future in- vestigators, and the possibility of extending it for use in more varied applications is also considered.